'Benefits Street' and the Myth of Workless Communities. (September 2014) - Macdonald, Robert; Shildrick, Tracy; Furlong, Andy
This paper critically engages with a pervasive myth about welfare in the UK which is commonly spread by politicians, think tanks and the media. This is the myth that there are areas of the country which are so affected by entrenched cultures of 'welfare dependency' that the majority of residents are unemployed. In undertaking research that sought to investigate a different idea - that there are families where no-one has worked over several generations - we simultaneously gathered evidence about the likelihood that there are localities where virtually no-one is in employment. The rationale for Channel 4's Benefits Street was exactly this; that whole streets and neighbourhoods are of out of work and living on welfare benefits. We draw on research evidence gathered in Middlesbrough and Glasgow to investigate this idea. Thus, the aim of our paper is simple and empirical: is the central idea of 'Benefits Street' true? Are there streets and neighbourhoods in the UK where virtually no-one works?